THE EFFECT OF AEROBIC CONTINUOUS AND INTERVAL TRAINING ON THE LEFT VENTRICULAR STRUCTURE AND FUNCTION OF MALE NON-ATHLETES - Toba Kazemi; Abbas Ali Gaeini; Javad Mahdiabadi; Mohammadali Mahdiabadi (Termedia Publishing House, 2013)
Exercise plays an important role to improve cardiovascular performance. The aim of this study was to compare the effect of aerobic continuous and interval training on the left ventricular structure and function. Twenty untrained healthy male students (aged 18-22 yrs.) were randomly divided into two groups: continuous (C; n=10) and interval (I; n=10). The training program consisted of running at 700of maximum heart rate (MHR) for 45 min during 8 weeks three times a week. In each session C group was running 45 min and I group running was done in 5 nine-minute stages with a four-minute inactive rest between them. M-mode, 2-dimensional, color and Doppler transthoracic echocardiography were performed, during resting conditions, before and after the training period. After 8-week training the end diastolic diameter, systolic blood pressure and diastolic blood pressure in C and I groups, the post-wall thickness and the end systolic diameter in I group showed no significant difference (P>0.05). On the other hand percent of ejection fraction and shortening fraction in C and I groups, the end systolic diameter and the post-wall thickness in C group and the interventricular septum thickness in I group demonstrated significant difference (P≤0.05). Comparing the two groups, only the value of the interventricular septum thickness was significant (P≤0.05). Eight-week aerobic continuous and interval training can affect left ventricular structure and function.